Open channel flow analysis of drains at Universiti Malaysia Pahang campus Pekan using Infoworks CS - Mohamad Hilman, Mohamed Sabri (2012)
Flood can be defined as an overflow of water from water body normally occurred when the water body can no longer contain the precipitation in the area and the soil can no longer absorb the water. This resulted in overflow and one of the causes of flood. The study area is Universiti Malaysia Pahang (UMP) campus Pekan where it is located in an area where flood occurrences are recorded each year with the main reason is overflow from the Pekan River. The soil condition in the area also poses problem where it is swampy and this type of soil have low porosity and can lead to increase in surface runoff. The objectives of this study is to develop and validate 2-Dimensional hydrological modeling of UMP Pekan drainage system using Infoworks CS and to determine the capabilities of existing drain to sustained runoff at maximum level. Data are obtained from (Jabatan Pembangunan dan Pengurusan Harta) JPPH UMP such as invert level, platform level, and plan view of study area. The study area which is 60 hectares area in total was divided into three zones; Zone A, Zone B and Zone C. In order to analyze the effectiveness of the drains at UMP Pekan, two method of calculation is used which are Rational Method for calculating the surface runoff and Manning Equation for the calculation of drain flowrate. Infoworks CS will be used to simulate the event of 8 hour rainfall with data obtained from MASMA with 2 ART. Water level is obtained after simulation process is completed. Result shows Zone C experienced overflow while Zone A drainage system experienced high water level that almost cause overflow. Only Zone B shows properly design drainage system where water level is in the mid-section of the drain. This result is proven both in manual calculation and software simulation.